Incisor proclination and gingival recessions: is there a relationship? - Márlio Vinícius de Oliveira; Matheus Melo Pithon; Márcia Luzia Lacerda Xavier; Rodrigo Villamarim Soares; Martinho Campolina Rebello Horta; Dauro Douglas Oliveira (Universidade Estadual de Campinas, 2017)
Aim: To test the hypothesis that there is no relationship between the amount of vestibular inclination of mandibular incisors and the appearance of gingival recession in this region. Methods: This study included 20 patients selected in accordance with the following inclusion criteria: 1. adult patients without gingival recession in the mandibular incisors before treatment (T0), 2. no previous orthodontic treatment, 3. treated without tooth extraction in the mandibular arch, 4. bonded mandibular splinting from one canine to another after the active stage of orthodontic treatment (T1), 5. no visible wear of the incisal edge of the mandibular incisors, 6. Pre- and post-treatment teleradiography and plaster casts, and plaster casts 3 years post-treatment (T2). Depending on the amount of inclination of the mandibular incisors after treatment, the sample was divided into two groups: Group 1- 10 individuals (IMPA T1-T0 ≤ 5˚) and Group 2- 10 individuals (IMPA T1-T0 > 5˚). The measurement of length of the clinical crown (LCC) of the four mandibular incisors, distance between the incisal edge and vestibular marginal gingiva were made in plaster casts at T0, T1 and T2. Results: In spite of Group 1 presenting a reduction in LCC at T2, there was no statistically significant difference in LCC in the 3 time intervals evaluated in the two groups. Conclusions: The null hypothesis was accepted. The variation in the amount of vestibular inclination of the mandibular incisors during orthodontic treatment and 3 years after conclusion of treatment did not promote the appearance of gingival recessions in this group of patients.